2017
DOI: 10.1111/jzs.12178
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and morphological discrimination of three species of ninespined stickleback Pungitius spp. (Teleostei, Gasterosteidae) in France with the revalidation of Pungitius vulgaris (Mauduyt, 1848)

Abstract: The taxonomy of French ninespined sticklebacks (Pungitius spp.) has long been controversial. To clarify the taxonomy in this group, we use mitochondrial (COI) and nuclear (RNF213) sequence markers, as well as morphological data. In France, both genetic markers discriminate three evolutionary lineages. Morphological analysis on fresh and type specimens supports the different lineages and the existence of three species in France. Pungitius pungitius, occurring in the North of France and Rhone basin, is character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 90 publications
(147 reference statements)
0
13
0
Order By: Relevance
“…The clearest case is the suggested transfer of the mitogenome from the Western European lineage of P. pungitius to P. laevis . As the two species are parapatric and co‐occur in several areas (Denys et al, ; Kottelat & Freyhof ; Wang et al, ), this scenario is biologically plausible. Theoretically, because the two species are also very closely related and diverged only 3.33 Mya, incomplete lineage sorting could also account for the fact that some individuals of P. laevis share the same mitochondrial haplotype with P. pungitius .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The clearest case is the suggested transfer of the mitogenome from the Western European lineage of P. pungitius to P. laevis . As the two species are parapatric and co‐occur in several areas (Denys et al, ; Kottelat & Freyhof ; Wang et al, ), this scenario is biologically plausible. Theoretically, because the two species are also very closely related and diverged only 3.33 Mya, incomplete lineage sorting could also account for the fact that some individuals of P. laevis share the same mitochondrial haplotype with P. pungitius .…”
Section: Discussionmentioning
confidence: 99%
“…Also, divergence among the three distinct P. laevis lineages (see also: Wang et al, ) was high (1.1%–1.8%), suggesting that P. laevis might actually contain more than one distinct species. However, according to the 3% demarcation criterion above, the different P. laevis lineages would still perhaps best be considered as a single species (but see: Denys et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Traditionally about 80 species were recognized [34], yet with the advent of the DNA barcoding and integrative taxonomy [44] several taxonomic revisions have been done: some new species have been described [45][46][47], others have been invalidated [48]. For instance, it was thought that the Northern pike (Esox Lucius) was the only species present in Europe, but recent integrative analyses based on both morphological and molecular characters concluded that three species are actually present in France, the Northern pike (which is the most common), E. aquitanicus (from the Charente to the Adour drainages), and E. cisalpinus (mostly in the Lake Geneva).…”
Section: Alien Species In Europe and Francementioning
confidence: 99%